Effect of Debt to Equity Ratio and Efficiency on Return on Equity in Defense Sector Companies - Buhroni, Akhmad Firmansyah; Yulivan, Ivan; Prakoso, Lukman Yudho (Journal Of Accounting Management Business And International Research, 2023)
Indonesia is a country that has so many islands, that's why Indonesia is often called a maritime country. In the Law of the Republic of Indonesia No. 16 of 2012 concerning the Defense Industry it is given to companies in the defense industry immediately, but rather a set of regulations, terms and conditions that must first be fulfilled by companies in the Defense Industry. The success of a company can be seen from the level of ROE or (Return On Equity). However, the Defense Sector Company's net profit from 2011-2020 is still relatively small. This study uses a quantitative approach. The samples used in this study were 3 companies including PT Dirgantara Indonesia, PT PAL Indonesia and PT Pindad with a period of 10 years. The results of this study indicate that DER has a negative effect on ROE, efficiency has a positive effect on ROE, and the magnitude of the influence of Debt To Equity Ratio (DER) and Efficiency on Return On Equity in defense sector companies is 66.3% and the remaining 33.7% is explained by the variable others that were not examined in this study.